Contextualization of Sunnah Ghairu Tasyri’ in the Perspective of Yusuf Al-Qardhawi - Alamsah, Johan; Anggun Puspita Ningrum (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract This research focuses on the perspective of Yusuf al-Qaradawi regarding sunnah ghairu tasyri', particularly the practice of eating with three fingers in the context of modern life. The writer uses a qualitative method with the analytical-descriptive approach to explore how Yusuf al-Qaradawi differentiates between sunnah related to Islamic law and those that are not. In developing the concept of hadith ghairu tasyri', this study emphasizes that sunnah is not limited only to matters of Islamic law but also has implications for ethics and morality. The importance of contextualizing the hadith about eating with three fingers lies in its key to understanding religious teachings within social, cultural, and contemporary settings. This helps to avoid extreme interpretations and highlights that hadith content should not be understood merely in a literal sense. Furthermore, this study underlines the educational values contained within it and points out the significance of the Sunnah as a guiding universal principle. The results of this research show that Yusuf al-Qaradawi's understanding of sunnah ghairu tasyri', especially regarding the hadith on eating with three fingers, reflects values such as patience, avoiding greed, and training in carefulness. In today's Islamic world, Yusuf al-Qaradawi's view on sunnah ghairu tasyri' encourages us to pursue broader knowledge without abandoning or being overly bound by traditions from the past. Keywords: Ghairu Tasyri’; Sunnah; Yusuf Al-Qaradawi. Abstrak Penelitian ini berfokus pada perspektif Yusuf al-Qaradhawi tentang sunnah ghairu thasri’ khususnya praktik makan dengan tiga jari dalam konteks kemodernan. Penulis menggunakan metode kualitatif dan deskriptif analitis untuk mengeksplorasi bagaimana Yusuf al-Qaradhawi membedakan antara sunnah yang berkaitan dengan hukum syariah dan yang tidak. Dalam menyempurnakan konsep hadits ghairu tashri’, penelitian ini menekankan bahwa sunnah tidak hanya terbatas pada hukum syariah saja namun juga berimplikasi pada etika dan moralitas. Pentingnya mengkontekstualisasikan hadis tentang makan dengan tiga jari menjadi kunci untuk memahami ajaran agama dalam konteks sosial, budaya, dan kekinian untuk menghindari penafsiran yang ekstrim dan mengakui bahwa isi hadis tidak boleh dipahami hanya secara harfiah. Lebih lanjut, kajian ini menekankan nilai-nilai pendidikan yang tertanam di dalamnya dan menggarisbawahi pentingnya sunnah sebagai prinsip pedoman universal. Hasil dari penelitian ini menunjukkan bahwa sunnah ghairu tasyri Yusuf Qordhowi khususnya terhadap hadits makan tiga jari menunjukkan adanya nilai-nilai kesabaran, menghindari sifat tamak dan melatih skill ketelitian. Kemudian dalam dunia Islam Kontemporer, sunnah ghairu tasyri Yusuf Qordhowi mendorong kita untuk memamahami ilmu yang lebih luas tanpa meninggalkan dan terpaku pada tradisi masa lalu. Kata Kunci: Ghairu Tasyri’; Sunnah; Yusuf Al-Qaradhawi.